2020
DOI: 10.1007/s00167-020-06091-5
|View full text |Cite
|
Sign up to set email alerts
|

Cementless unicompartmental knee replacement achieves better ten-year clinical outcomes than cemented: a systematic review

Abstract: The aim of this study was to report and compare the long term revision rate, revision indications and patient reported outcome measures of cemented and cementless Unicompartmental knee replacements (UKR).Methods: Databases Medline, Embase and Cochrane Central of Controlled Trials were searched to identify all UKR studies reporting the ≥10 year clinical outcomes. Revision rates per 100 component years (% per annum (%pa)) were calculated by fixation type and then subgroup analysis for fixed and mobile bearing UK… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 68 publications
(172 reference statements)
1
16
0
Order By: Relevance
“…In addition, a recent level III systematic review evaluated the effect of cementing in 10,736 UKAs and found that cementless UKA was associated with lower revision rate than the cemented UKA (0.45% pa vs 0.73% per annum , p < 0.001). However, this difference was insignificant ( p = 0.41) in the non-Oxford UKAs with similar revision rates of cemented and cementless UKRs (0.57% pa vs 0.69% pa) [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a recent level III systematic review evaluated the effect of cementing in 10,736 UKAs and found that cementless UKA was associated with lower revision rate than the cemented UKA (0.45% pa vs 0.73% per annum , p < 0.001). However, this difference was insignificant ( p = 0.41) in the non-Oxford UKAs with similar revision rates of cemented and cementless UKRs (0.57% pa vs 0.69% pa) [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similar excellent mid- to long-term results are shown in a number of other recent studies on cementless UKA. 9 , 38 , 39 …”
Section: Uka Outcomesmentioning
confidence: 99%
“…Mohammad et al 9 undertook a pooled analysis of 8,760 cemented and 1,946 cementless UKAs, and reported ten-year survivorship was 92.7% and 95.5%, respectively (p < 0.001). The authors reported improved revision rates in cementless mobile-bearing UKAs relative to cemented, but consistent revision rates among fixed-bearing UKAs regardless of cementation group.…”
Section: Uka Outcomesmentioning
confidence: 99%
See 1 more Smart Citation
“…This conclusion was also reflected in other recent findings. For example, Mohammad et al [ 14 ] found lower long-term revision rates for cementless UKA compared with cemented UKA and positive results for cementless UKA for all age groups [ 15 ]. Basso and colleagues [ 5 ] reported that using a cementless fixation could possibly improve survival rate by reducing problems associated with the cement, such as inappropriate penetration and loose fragments.…”
Section: Introductionmentioning
confidence: 99%